(3cJGH GdejSQ hGdbOGMs - (3YHO Gddg Hf eSde Hf bJjHI GdOjnfnhQqj, CHh eMeO, GHf obnJrjnHI, J (B276 (3g` s ((3eMeO CHj GdYjfjf YWjI s)
(3ChdgG (B:s
(3CeG HYO aEfc cJHJ JYdefi JYdb bdHc HGdejSQ hcjajJg hGdbOGM hNWhWgG s
(3BNQgG (B:s
(3HGH GdYTQI Hjb hGdMeO ddg hMOg hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde hMSHfG Gddg hfYe Gdhcjd s
(3HChdg agQSJ ddeNWhWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B137s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1465s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3CdYGH JjehQ (B27) s
Keywords: (3GdTWQfLs